TLR2 mediates autophagy through ERK signaling pathway in Mycoplasma gallisepticum-infected RAW264.7 cells. (July 2017) - Lu, Ziyin; Xie, Daoyuan; Chen, Ying; Tian, Erjie; Muhammad, Ishfaq; Chen, Xueping; Miao, Yusong; Hu, Wanjun; Wu, Ziyong; Ni, Huili; Xin, Jiuqing; Li, Yuan; et al.
Highlights: In this study, we examined autophagy and multiple signaling pathways by employing MG infected mouse macrophage cell line RAW264.7. MG infection activated autophagy and mitogen-activated protein kinase (MAPKs) in RAW264.7 cells. We explored for the first time that TLR2 may mediate MG-induced autophagy via ERK signaling pathway in macrophages. Abstract: Toll-like receptor 2 (TLR2) plays a crucial role in early innate immune response of host to various microorganisms. Mycoplasma gallisepticum (MG) is one of the major pathogen that can cause chronic respiratory diseases in chickens, but the molecular mechanism of MG infection still remained unclear. In this study, we examined the typical hallmarks of autophagy and multiple signaling pathways by western blot, immunofluorescence microscopy and electron microscopy. The results indicated that infection of mouse macrophage cell line RAW264.7 with MG activated autophagy and mitogen-activated protein kinases (MAPKs). Silencing of TLR2 by siRNA substantially down-regulated MG-triggered autophagy in macrophages, and markedly reduced MG-induced extracellular regulated protein kinase (ERK) in macrophages but did not down-regulate c-Jun N-terminal kinase (JNK) and p38. Importantly, in macrophages, inhibition of ERK by PD98059 (ERK inhibitor) also significantly attenuated the level of autophagy upon MG infection, and the simultaneous treatment of TLR2 siRNA and PD98059 showed a similar effect on MG-induced autophagy as compared with TLR2 siRNA treatment alone. These findings thus demonstrate that TLR2 may mediate MG-induced autophagy through ERK signaling pathway in macrophage.